EXPERIMENTAL STUDY OF EFFECTIVENESS OF DEEP FLUORIDATION OF ENAMEL DURING SECONDARY MINERALIZATION OF THE PERMANENT TEETH ENAMEL - H. V. Sorochenko (Ukrainian Medical Stomatological Academy, 2016)
Introduction. Increased risk of dental caries of permanent teeth in childhood corresponds to the period of secondary mineralization (5-15 years). The main pathogenetic direction of caries prevention in this period is to increase the level of mineralization of tooth enamel. High efficiency of caries prevention with fluoride preparations is associated with exposure to fluoride at different stages of dental caries pathogenesis, including the kinetics of the process of mineralization. Among the advantages of method of deep fluoridation of enamel (A.Knappvost, 1986) there are its painlessness, duration (3 minutes) and multiplicity of procedures (once every 6 months). The aim of the research was in vitro investigation of changes in chemical composition and morphological structure of the superficial layer of just erupted permanent teeth enamel under the influence of deep fluoridation. Object and methods of the research. We examined 15 samples of permanent teeth enamel (erupted not later than 6 months before research, premolars of children aged 11-13). All samples were randomly divided into 3 groups and stored in 3 separately sealed boxes (5 in each box) with artificial saliva (T. Fusayama, 1975). Enamel samples of the first group were investigated at the beginning of the experiment. Enamel samples of the second group were treated with medication for deep fluoridation of enamel "Ftorcalcit E". Samples were treated at the beginning of experiment and after 6 month of experiment. Enamel samples of the third group were the control ones and they were not treated. Enamel samples of the second and third group were investigated at the end of experiment. Enamel samples were studied at the beginning of the experiment and 6 months later. Surface of the samples at the first stage of the research was analyzed by scanning electron microscope (SEM, INCA PENTA FET×3, Oxford Instruments, Co., UK), at the second stage quantitative chemical composition was determined by X-ray photoelectron spectroscopy (X-ray, EDS) with Auger microprobe JAMP -9500F (Japan). The results were calculated in weight percentage. The research results prove that 6 months after the procedure of deep fluoridation significant changes in content of calcium (from 20.47±1.07 to 28.5±1.05), oxygen (from 54.09±6.08 to 35.5±3.75), carbon (from 8.22±0.73 to 5.7±0.52), fluorine (from 0.1±0.03 to 12.5±1.97), magnesium (from 0.21±0.04 to 0.7±0.09), sodium (from 0.58±0.07 to 0.3±0.05), silicon (from 0.02±0.009 to 1.33±0.17), calcium/phosphorus ratio (from 1.38±0.08 to 2.11±0.12 ) take place in the superficial layer of immature permanent teeth enamel (р<0.05). Increased mineralization of the permanent teeth enamel after deep fluoridation was confirmed by scanning electron microscopy data. After deep fluoridation of enamel, the relief of enamel smoothed, surface looked lighter. There was closure of significant part of craters of enamel prisms or substantial reduction of unclosed surfaces as compared to the initial level. Conclusions. Thus, the results of the study indicate that enamel of just erupted teeth is not mineralized and thus has insufficient resistance to caries. The chemical composition of the superficial layer of tooth enamel changed after using of methods of deep fluoridation of enamel. Achieving of the optimal level of mineralization under the influence of deep fluoridation occurs within 6-months of the experiment. Thus, exogenous agents for the prevention of dental caries (deep fluoridation of enamel) can be recommended for clinical use immediately after the eruption of the teeth within 12 months (1-2 times per year).